The diverse morphology of pockmarks around Aotearoa New Zealand - Hillman, Jess I. T.; Watson, Sally Joan; Maier, Katherine Leigh; Hoffmann, Jasper Justus Lutz; Bland, Kyle J.; Warnke, Fynn; Pecher, Ingo A.; Gorman, Andrew Robert; Davy, Bryan; Bull, Suzanne; Woelz, Susi (Frontiers in Marine Science, 2023)
Seafloor pockmarks are abundant around Aotearoa New Zealand, occurring across a diverse range of tectonic, sedimentological and geomorphological settings. Globally, the formation and source of pockmarks is widely researched because they: 1) have potential links to subsurface hydrocarbon systems, 2) can provide important habitats for benthic organisms and 3) may be indications of fluid escape pathways or areas of sediment disturbance, which influence seafloor stability and could pose a risk to infrastructure. Pockmarks are widely associated with fluid release (such as gas or water) from subsurface reservoirs. However, the formation of pockmarks, the processes that shape and modify their morphology over time, and the relative timing of these events, remains enigmatic. Here, we compile the first national database of over 30,000 pockmarks around Aotearoa New Zealand, allowing us to begin to comprehend the dynamic processes that shape and affect pockmarks by exploring regional and inter-regional patterns in pockmark geometry and seabed characteristics. This compilation reveals several significant trends, including a distinct lack of correlation between active seafloor seeps and pockmarks, and a strong association of pockmarks with mud-rich seafloor substrate. Furthermore, we highlight key knowledge gaps that require further investigation moving forward, including a lack of constraint on the timing of pockmark formation, and limited modelling of the processes involved in their formation.